Emergence of invasive candidiasis with multiple Candida species exhibiting azole and echinocandin resistance - Huang, Si-Jia; Song, Yi-Hui; Lv, Geng; Liu, Jin-Yan; Zhao, Jun-Tao; Wang, Lu-Ling; Xiang, Ming-Jie (Frontiers in Microbiology, 2025)
BackgroundInvasive candidiasis (IC) is an increasingly common, expensive, and potentially fatal infection. However, IC caused by multiple Candida species is rarely reported in China. Herein, we revealed a complex IC caused by multiple Candida species, comprising the rare C. norvegensis, C. albicans, C. glabrata, and C. tropicalis. The resistance mechanism of azole and echinocandin resistance were explored further.MethodsThe isolates were confirmed using internal transcribed spacer (ITS) sequencing. The resistance mechanisms were investigated using PCR-based sequencing, quantitative real-time reverse transcription PCR, and rhodamine 6G efflux quantification.ResultsAntifungal susceptibility testing showed this complex infection was associated with cross-resistance to azole and echinocandin drugs. For C. glabrata, the acquired echinocandin resistance was likely caused by a novel mutational pattern (1,3-beta-D-glucan synthase subunits FKS1-S629P and FKS2-W1497stop) while the acquired azole resistance in C. glabrata RJ05 was related to complex mechanisms including enhanced efflux activity, pleiotropic drug resistance 1 (PDR1) mutation, and increased expression of Candida drug resistance 1 (CDR1) and CDR2. Additionally, the azole resistance of C. tropicalis was caused by two lanosterol 14-alpha demethylase (ERG11) mutations: Y132F and S154F.ConclusionOur study revealed a case of clinically complex, multiple Candida invasive infections, further uncovering the resistance mechanisms to azoles and echinocandins. These findings provide valuable references for the diagnosis and treatment of invasive candidiasis (IC) in clinical practice.